Suitability of Geospatial-Based Land Use on River Borders in The Tallo Watershed - Amaliah, Rizki; Wahyuni; Jelsy, Vresilia; Kadir, Muh Ichsan (Fakultas Kehutanan, Universitas Hasanuddin, 2025)
Riverbank areas play a vital role in maintaining river ecosystems, such as reducing the risk of natural disasters such as flooding and erosion and protecting water quality. Inappropriate land use in riverbank areas can cause environmental damage and increase disaster risks. This study aims to identify land use and land use suitability in the main riverbanks in the Tallo Watershed using Geographic Information Systems (GIS) and adjusted based on laws and regulations. The results show that the dominant land use in the Tallo Watershed riverbanks is horticultural dry fields, amounting to 188.51 ha, or 40.92% of the area of the Tallo Watershed riverbank area. The use of riparian land that complies with regulations is 26.08%, and the use that does not comply is 73.92%.